Involvement of Lipocalin‐like CghA in Decalin‐Forming Stereoselective Intramolecular [4+2] Cycloaddition. Issue 16 (2nd October 2015) - Sato, Michio; Yagishita, Fumitoshi; Mino, Takashi; Uchiyama, Nahoko; Patel, Ashay; Chooi, Yit‐Heng; Goda, Yukihiro; Xu, Wei; Noguchi, Hiroshi; Yamamoto, Tsuyoshi; Hotta, Kinya; Houk, Kendall N.; et al.
Abstract Understanding enzymatic Diels–Alder (DA) reactions that can form complex natural product scaffolds is of considerable interest. Sch 210972 1, a potential anti‐HIV fungal natural product, contains a decalin core that is proposed to form through a DA reaction. We identified the gene cluster responsible for the biosynthesis of 1 and heterologously reconstituted the biosynthetic pathway in Aspergillus nidulans to characterize the enzymes involved. Most notably, deletion of cghA resulted in a loss of stereoselective decalin core formation, yielding both an endo (1) and a diastereomeric exo adduct of the proposed DA reaction. Complementation with cghA restored the sole formation of 1. Density functional theory computation of the proposed DA reaction provided a plausible explanation of the observed pattern of product formation. Based on our study, we propose that lipocalin‐like CghA is responsible for the stereoselective intramolecular [4+2] cycloaddition that forms the decalin core of 1.